2005
DOI: 10.1136/adc.2004.052670
|View full text |Cite
|
Sign up to set email alerts
|

Case gender and severity in cerebral palsy varies with intrauterine growth

Abstract: Background: There is an unexplained excess of cerebral palsy among male babies. There is also variation in the proportion of more severe cases by birth weight. It has recently been shown that the rate of cerebral palsy increases as intrauterine size deviates up or down from an optimum about one standard deviation heavier than population mean weight-for-gestation. Aims: To determine whether the gender ratio or the severity of cases also varies with intrauterine size. Methods: A total of 3454 cases of cerebral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 27 publications
2
77
1
Order By: Relevance
“…Additionally, there is an unexplained excess of CP among male infants. 36 The sexassociated difference in susceptibility indicates that the cause of CP may be different in males and females. Thus, subgroup analysis by sex may be helpful to identify the cause of CP.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is an unexplained excess of CP among male infants. 36 The sexassociated difference in susceptibility indicates that the cause of CP may be different in males and females. Thus, subgroup analysis by sex may be helpful to identify the cause of CP.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the underlying mechanisms leading to such sex differences; however, animal studies have shown that the endogenous reaction to developmental injury is highly dependent on sex [20]. In a large European study involving 4,500 infants with cerebral palsy, incidence rates were 30% higher in males than females [21]; the EPICure Study reported similar differences, including lower cognitive scores at the age of 6 years in males [22]. A recent meta-analysis reported higher full-scale IQ scores in females born prematurely compared to matched males [23].…”
Section: Discussionmentioning
confidence: 99%
“…Increased incidence of CP supposedly correlates with increased survival rates of premature or low birth weight children Cerebral Palsy most commonly experienced by male infants. In a study conducted by Johnstoneand Hagberg (2007); Jarvis et al, (2005) CP cases is more commonly observed in male gender as much as 30% when compared with female gender.…”
Section: Introductionmentioning
confidence: 96%